Ubr3 E3 ligase regulates apoptosis by controlling the activity of DIAP1 in Drosophila. - Huang, Q.; Tang, X.; Wang, G.; Fan, Y.; Ray, L.; Bergmann, A.; Belenkaya, T.Y.; Ling, X.; Yan, D.; Lin, Y.; Ye, X.; Shi, W.; et al. (Cell Death and Differentiation, 2014)
Apoptosis has essential roles in a variety of cellular and developmental processes. Although the pathway is well studied, how the activities of individual components in the pathway are regulated is less understood. In Drosophila, a key component in apoptosis is Drosophila inhibitor of apoptosis protein 1 (DIAP1), which is required to prevent caspase activation. Here, we demonstrate that Drosophila CG42593 (ubr3), encoding the homolog of mammalian UBR3, has an essential role in regulating the apoptosis pathway. We show that loss of ubr3 activity causes caspase-dependent apoptosis in Drosophila eye and wing discs. Our genetic epistasis analyses show that the apoptosis induced by loss of ubr3 can be suppressed by loss of initiator caspase Drosophila Nedd2-like caspase (Dronc), or by ectopic expression of the apoptosis inhibitor p35, but cannot be rescued by overexpression of DIAP1. Importantly, we show that the activity of Ubr3 in the apoptosis pathway is not dependent on its Ring-domain, which is required for its E3 ligase activity. Furthermore, we find that through the UBR-box domain, Ubr3 physically interacts with the neo-epitope of DIAP1 that is exposed after caspase-mediated cleavage. This interaction promotes the recruitment and ubiquitination of substrate caspases by DIAP1. Together, our data indicate that Ubr3 interacts with DIAP1 and positively regulates DIAP1 activity, possibly by maintaining its active conformation in the apoptosis pathway.